Diagnostic Accuracy of Ultrasonography for Rotator Cuff Tears: A Systematic Review and Meta-analysis. Issue 10 (8th October 2021) - Farooqi, Ali S.; Lee, Alexander; Novikov, David; Kelly, Ann Marie; Li, Xinning; Kelly, John D.; Parisien, Robert L.
Background: With recent improvements in transducer strength, image resolution, and operator training, ultrasound (US) provides an excellent alternative imaging modality for the diagnosis of rotator cuff tears. Purpose: To evaluate the diagnostic accuracy of US for partial- and full-thickness rotator cuff tears and biceps tendon tears, compare diagnostic values with those of magnetic resonance imaging (MRI) using arthroscopy as the reference standard, assess longitudinal improvements in accuracy, and compare diagnostic values from operators with different training backgrounds. Study Design: Systematic review; Level of evidence, 3. Methods: The PubMed and Cochrane Library databases were systematically searched for full-text journal articles published between January 1, 2010, and April 1, 2020. The inclusion criteria were studies that evaluated the diagnostic accuracy of US for rotator cuff tears or biceps tendon tears utilizing arthroscopy as the reference standard. The exclusion criteria were studies with <10 patients, studies including massive tears without reporting diagnostic data for specific tendons, and studies lacking diagnostic outcome data. Extracted outcomes included diagnostic accuracy, sensitivity, specificity, negative predictive value, and positive predictive value. The mean difference and 95% confidence interval were calculated for both US and MRI diagnostic values, and meta-analysis was conducted using the Mantel-Haenszel random-effects model. Results: In total, 23 eligible studies involving 2054 shoulders were included. US demonstrated a higher median diagnostic accuracy for supraspinatus tendon tears (0.83) and biceps tendon tears (0.93) as compared with subscapularis tendon tears (0.76). US was found to have a higher median accuracy (0.93) for full-thickness supraspinatus tears than partial-thickness tears (0.81). US had superior median sensitivity for partial-thickness supraspinatus tears when performed by radiologists as opposed to surgeons (0.86 vs 0.57). Meta-analysis of the 5 studies comparing US and MRI demonstrated no statistically significant difference in diagnostic sensitivity, specificity, or accuracy for any thickness supraspinatus tears (P = .31-.55), full-thickness tears (P = .63-.97), or partial-thickness tears ( P = .13-.81). Conclusion: For experienced operators, US is a highly sensitive and specific diagnostic modality for the diagnosis of supraspinatus tears and demonstrates statistically equivalent capability to MRI in the diagnosis of both full- and partial-thickness rotator cuff tears.